Death talk : the case against euthanasia and physician-assisted suicide - Somerville, Margaret A. (CEL - Canadian Publishers Collection., 2001)
There are vast ethical, legal, and social differences between natural death and euthanasia. In Death Talk Margaret Somerville argues that legalizing euthanasia would cause irreparable harm to society's value of respect for human life, which in secular societies is carried primarily by the institutions of law and medicine.